Dendritic cell entry to lymphatic capillaries is orchestrated by CD44 and the hyaluronan glycocalyx - Johnson, LA; Banerji, S; Lagerholm, BC; Jackson, DG (Life Science Alliance, 2021)
DCs play a vital role in immunity by conveying antigens from peripheral tissues to draining lymph nodes, through afferent lymphatic vessels. Critical to the process is initial docking to the lymphatic endothelial receptor LYVE-1 via its ligand hyaluronan on the DC surface. How this relatively weak binding polymer is configured for specific adhesion to LYVE-1, however, is unknown. Here, we show that hyaluronan is anchored and spatially organized into a 400–500 nm dense glycocalyx by the leukocyte receptor CD44. Using gene knockout and by modulating CD44-hyaluronan interactions with monoclonal antibodies in vitro and in a mouse model of oxazolone-induced skin inflammation, we demonstrate that CD44 is required for DC adhesion and transmigration across lymphatic endothelium. In addition, we present evidence that CD44 can dynamically control the density of the hyaluronan glycocalyx, regulating the efficiency of DC trafficking to lymph nodes. Our findings define a previously unrecognized role for CD44 in lymphatic trafficking and highlight the importance of the CD44:HA:LYVE-1 axis in its regulation.